The Modified Pell and the Modified k-Pell Quaternions and Octonions - Catarino, Paula (2017)
In this paper we consider the Modified Pell and the Modified k-Pell quaternions and octonions and we present some properties involving these sequences, including the Binet-style formulas and the ordinary generating functions.